Neurocognitive characterization of behaviour and mental illness through time-varying brain network analysis - Chang, Xiao; Jia, Tianye; Fu, Zening; Xiang, Shitong; Xia, Yunman; Xie, Chao; Zou, Jiyan; Cao, Miao; Zhang, Jie; Banaschewski, Tobias; Bokde, Arun L. W.; Desrivières, Sylvane; et al. (Nature Communications, 2026)
Human cognitive processing involves dynamic interactions across brain regions, evolving over time. Traditional neuroimaging analysis often overlooks this temporal aspect, limiting insights into how functional network connectivity (FNC) supports ongoing cognition and behaviour. Using sliding window analysis, we captured FNC changes during tasks, reflecting network reconfiguration in cognitive processes. We further determined behavioural relevance of time-varying FNC by relating network measurements with task performances and psychopathology. We found that several whole-brain FNC patterns, or states, persist across resting and task-based fMRI, with state occurrences fluctuating with the most prominent task stimuli. Regional FNC distinguishes specific task conditions, and time-varying FNC explains more variance in psychopathology symptoms compared to static connectivity. These findings highlight that cognitive tasks reshape regional and whole-brain connectivity. By considering the different FNC states, time-varying connectivity provides a more comprehensive representation of brain interactions and thus may represent a better neural proxy for cognition and behaviour.
Gesehen am 26.02.2026